Pembelajaran Kontekstual: Solusi Untuk Meningkatkan Kualitas Pendidikan - Jumadil Hamid; Pebriyan Pebriyan; Gusmaneli Gusmaneli (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2024)
Effective and efficient learning will encourage the achievement of educational goals. Learning must be managed well by paying attention to various strategies that are appropriate to the material being taught. One of them is a contextual learning strategy, which is deemed appropriate to the implementation of the curriculum. Contextual learning is a learning concept that helps teachers link the material taught with students' real-world situations and make connections between the knowledge they have and its application in real life. This learning emphasizes the process rather than the results, so that knowledge is formed in real terms by what is done and not just by memorizing concepts. According to contextual learning, knowledge will be meaningful when it is discovered and built by students themselves. For this, teachers need to understand students' learning types so that their teaching style can adapt to students' learning styles